Untargeted metabolomics analysis of the hippocampus and cerebral cortex identified the neuroprotective mechanisms of Bushen Tiansui formula in an aβ25-35-induced rat model of Alzheimer’s disease - Li, Hongli; Tan, Yejun; Cheng, Xin; Zhang, Zheyu; Huang, Jianhua; Hui, Shan; Zhu, Lemei; Liu, Yuqing; Zhao, Di; Liu, Zhao; Peng, Weijun (Frontiers in Pharmacology, 2022)
Background: Bushen Tiansui Formula (BSTSF) is a traditional formulation of Chinese medicine that has been used to treat Alzheimer’s disease (AD) for decades; however, the underlying mechanisms by which this formula achieves such therapeutic effects have yet to be elucidated. Prupose: To investigate the neuroprotective mechanisms of BSTSF against AD by analyzing metabolite profiles in the hippocampus and cortex of AD rats. Methods: The rat models of AD were established by the injection of Aβ25–35. The Morris water maze (MWM) test was performed to evaluate the effect of BSTSF treatment on cognitive dysfunction. Hematoxylin and eosin (HE) staining was used to assess the effect of BSTSF on typical AD pathologies. Underlying mechanisms were investigated using LC-MS/MS-based untargeted metabolomics analysis of the cerebral cortex and hippocampus. Results: BSTSF significantly improved memory deficits and the typical histopathological changes of AD rats. Untargeted metabolomics analysis showed that 145 and 184 endogenous metabolites in the cerebral cortex and hippocampus, respectively, were significantly different in the BSTSF group when compared with the AD group. The differential metabolites in the cerebral cortex were primarily involved in cysteine and methionine metabolism, while those in the hippocampus were mainly involved in D-Glutamine and D-glutamate metabolism. Conclusion: In the present study, we confirmed the neuroprotective effects of BSTSF treatment against AD using a rat model. Our findings indicate that the BSTSF-mediated protective effects were associated with amelioration of metabolic disorders in the hippocampus and cerebral cortex. Keywords: Alzheimer's disease; Bushen Tiansui Formula; Cerebral cortex; Hippocampus, metabolomics